Study on the Effects of Non Surgical Periodontal Therapy on Salivary pH: A Randomized Clinical Approach - Gupta, Stuti; Shradha, .; Sharma, Ejya; Gupta, Radhika; Sharma, Himani; Srivastava, Saransh (Recent Developments in Medicine and Medical Research Vol. 15, 2021)
Aim: The aim of the study is to assess the effect of non surgical periodontal disease on Salivary pH in patients reporting to the dental hospital. Objectives: The objective of the study is to assess the effects of Periodontal diseases and Non Surgical. Periodontol Therapy on Salivary pH. Also, the authors are trying to assess the influence of frequency of dental visits on periodontal disease status. Materials and Methods: Patient reporting to the Department of Periodontology, Dental Hospital In Greater Noida were recruited in the study. Its a randomized clinical trial where patients are randomized into two groups of Chronic Generalized Gingivitis and Chronic Generalized Periodontitis. Sample Size: 30 patients. Period of Study: 2 months. Clinical parameters are recorded and NSPT is done. Unstimulated Saliva is collected pre and post (14 days) non-surgical periodontal therapy. pH is determined using a pH meter. Data is collected and statistically interpreted. Statstical Testing to be Used: - Mann Whitney U Test - Chi- square test - Paired t-test Results: There was statistically significant difference in plaque index, gingival index and oral hygiene index in two groups. There was a definite reduction in pH levels post SRP but it was statistically non significant due to relatively smaller sample size. Further research is required to substantiate the results.